2015
DOI: 10.1039/c5cp00850f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational composition, molecular structure and decomposition of difluorophosphoryl azide in the gas phase

Abstract: The conformational composition, molecular structure and decomposition of difluorophosphoryl azide F2P(O)N3 in the gas phase were studied using gas electron diffraction (GED), matrix isolation IR spectroscopy, and quantum-chemical calculations, respectively. While computational methods predict only minor differences in the total energy between the two possible conformers (syn and anti), the analysis of electron diffraction data reveals the dominating abundance of the syn conformer in the gas phase at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…In contrast, the symmetric N 3 stretching mode is located at 1251.8 cm −1 due to distinct 15 N‐isotope shifts of 9.9 and 26.0 cm −1 (Figure S6) for the two pairs of 15 N‐labeled nitrene isotopomers. Unlike the thermal persistency of the perfluorinated phosphoryl nitrene F 2 P(O)N in the gas phase, the absence of CH 3 OP(O)(N 3 )N among the HVFP products of CH 3 OP(O)(N 3 ) 2 indicates its fragmentation (→ CH 3 OPO + 2 N 2 ) under the pyrolysis conditions. Upon 365 nm UV‐light irradiation in N 2 matrix, CH 3 OP(O)(N 3 )N undergoes additional homolytic P−N bond cleavage, forming .…”
Section: Methodsmentioning
confidence: 98%
“…In contrast, the symmetric N 3 stretching mode is located at 1251.8 cm −1 due to distinct 15 N‐isotope shifts of 9.9 and 26.0 cm −1 (Figure S6) for the two pairs of 15 N‐labeled nitrene isotopomers. Unlike the thermal persistency of the perfluorinated phosphoryl nitrene F 2 P(O)N in the gas phase, the absence of CH 3 OP(O)(N 3 )N among the HVFP products of CH 3 OP(O)(N 3 ) 2 indicates its fragmentation (→ CH 3 OPO + 2 N 2 ) under the pyrolysis conditions. Upon 365 nm UV‐light irradiation in N 2 matrix, CH 3 OP(O)(N 3 )N undergoes additional homolytic P−N bond cleavage, forming .…”
Section: Methodsmentioning
confidence: 98%
“…[13] The isocyanate group in all cases is almost linear, i. e. ∡(NCO) is always larger than 170°, and the bond lengths in this unit do not vary much in the examples listed in Table 2. [38] Comparing the PÀ S bond length to the analogous distances in PF 2 H(S), PClF 2 (S) and PBrF 2 (S) the reported r a values (1.876(3), 1.864(8) and 1.881(4) Å, respectively) [39] the one determined for F 2 P(S)NCO (1.874(1) Å) is most similar to the length found for the hydrogen compound PF 2 H(S). The PÀ N bond length of F 2 P(S)NCO is also the shortest among the examples listed in Table 2.…”
Section: Gas-phase Structurementioning
confidence: 99%
“…Curtius rearrangement is the production of N 2 + RNCO (isocyanate) from carbonyl azides RC­(O)­N 3 upon thermal or photochemical excitation. This reaction is useful in many areas of synthetic chemistry including medicinal chemistry. Several experimental and theoretical studies investigating the mechanism of the Curtius reaction have been reported in the literature. Two mechanisms, viz., a stepwise and a concerted pathway have been proposed. The stepwise mechanism involves the formation of a nitrene RC­(O)N by N 2 elimination, followed by an intramolecular rearrangement of the nitrene, yielding the isocyanate.…”
Section: Introductionmentioning
confidence: 99%